Cervical Cancer Stem-Like Cell Transcriptome Profiles Predict Response to Chemoradiotherapy - Zuccherato, Luciana W.; Machado, Christina M. T.; Magalhães, Wagner C. S.; Martins, Patrícia R.; Campos, Larissa S.; Braga, Letícia C.; Teixeira-Carvalho, Andrea; Martins-Filho, Olindo A.; Franco, Telma M. R. F.; Paula, Sálua O. C.; da Silva, Israel Tojal; Drummond, Rodrigo; et al. (Frontiers in Oncology, 2021)
Cervical cancer (CC) represents a major global health issue, particularly impacting women from resource constrained regions worldwide. Treatment refractoriness to standard chemo-radiotherapy has identified cancer stem cells as critical coordinators behind the biological mechanisms of resistance, contributing to CC recurrence. In this work, we evaluated differential gene expression in cervical cancer stem-like cells (CCSC) as biomarkers related to intrinsic chemoradioresistance in CC. A total of 31 patients with locally advanced CC and referred to Mário Penna Institute (Belo Horizonte, Brazil) from August 2017 to May 2018 were recruited for the study. Fluorescence-activated cell sorting (FACS) was used to enrich CD34+/CD45- CCSC from tumor biopsies. Transcriptome was performed using ultra-low input RNA sequencing and differentially expressed genes (DEGs) using Log2 fold differences and adjusted p value < 0.05 were determined. A panel of biomarkers was selected using the rank-based AUC (Area Under the ROC Curve) and pAUC (partial AUC) measurements for diagnostic sensitivity and specificity. The analysis showed 1062 DEGs comparing between the Non-Responder (n=10) and Responder (n=21) groups to chemoradiotherapy. Overlapping of the 20 highest AUC and pAUC values revealed five transcripts potentially implicated in innate chemoresistance (ILF2, SNX2, COPZ1, AC016722.1 and AL360175.1). This study identifies DEG signatures that serve as potential biomarkers in CC prognosis and treatment outcome, as well as identifies potential alternative targets for cancer therapy.